2021
DOI: 10.46754/jssm.2021.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Household Waste Management Strategy Toward Zero Waste City: A Case Study of Banda Aceh

Abstract: The list of waste management services offered by the government are growing, but the generation of urban solid wastes is also on the rise. The aim of this study is to develop a strategy to manage household wastes in the city of Banda Aceh based on the five aspects of policy, institutional, funding, community participation, and operational technique. The study was conducted using in-depth interviews with waste management experts and a reviews of national and municipal policy documents dealing with waste managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…As a result, this research was conducted using an online survey distributed to 407 college students located throughout Indonesia. Numerous questions about food waste processing at the home level were asked to respondents, including sociodemographic factors, waste management knowledge, and community food handling practices (Mattar et al, 2018;Nizar et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, this research was conducted using an online survey distributed to 407 college students located throughout Indonesia. Numerous questions about food waste processing at the home level were asked to respondents, including sociodemographic factors, waste management knowledge, and community food handling practices (Mattar et al, 2018;Nizar et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…According to the survey, up to 170 respondents felt that waste sorting takes a long time and is difficult to accomplish. Public understanding of waste management in poor nations must still be improved in order to raise public awareness (Nizar et al, 2021).…”
Section: College Students' Knowledge Of Household Waste Managementmentioning
confidence: 99%
“…The study concluded that there were many areas which needed urgent consideration. Nizar et al (2021) worked on "Household Waste Management Strategy Towards Zero Waste City: A Case Study of Banda Aceh". The study was conducted using interviews with waste management experts.…”
Section: Chavan Et Al (2013) Worked On "A Case Study On Municipal Sol...mentioning
confidence: 99%
“…Handling activities include sorting, reuse and recycle to reduce the amount of waste generation (reduce). Waste collection is an activity carried out from homes or sources of waste generation to Temporary Shelters (TPS) before transportation or transfer of waste from TPS to the final processing location (TPA) (Alonso-Muñoz et al, 2022;Asteria & Herdiansyah, 2022;Kalempouw, 2021;Nizar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%